2018
DOI: 10.1111/bdi.12659
|View full text |Cite
|
Sign up to set email alerts
|

Investigating polygenic burden in age at disease onset in bipolar disorder: Findings from an international multicentric study

Abstract: The current study is the largest conducted so far to investigate the association between the cumulative BD and SCZ polygenic risk and AAO in BD patients. The reported negative results suggest that such a polygenic influence, if there is any, is not large, and highlight the importance of conducting further, larger scale studies to obtain more information on the genetic architecture of this clinically relevant phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
5
16
0
2
Order By: Relevance
“…Calafato and colleagues used, as mentioned before, the PGRS for schizophrenia to identify psychotic disorders [69] . The PGRS can also be used to investigate traits like age at onset e.g., Kalman and colleagues investigated the PGRS for schizophrenia and BD in synopsis with age at onset, but with negative results [72] . Groundbreaking results were also achieved by the PGC to either distinguish BD and schizophrenia and on the other hand to search for shared pathways-114 genome-wide significant loci were shared between schizophrenia and BD in a sample comprising of 53,555 individuals with BD or schizophrenia and 54,065 controls.…”
Section: Polygenic Risk Score For Schizophrenia In Bdmentioning
confidence: 99%
“…Calafato and colleagues used, as mentioned before, the PGRS for schizophrenia to identify psychotic disorders [69] . The PGRS can also be used to investigate traits like age at onset e.g., Kalman and colleagues investigated the PGRS for schizophrenia and BD in synopsis with age at onset, but with negative results [72] . Groundbreaking results were also achieved by the PGC to either distinguish BD and schizophrenia and on the other hand to search for shared pathways-114 genome-wide significant loci were shared between schizophrenia and BD in a sample comprising of 53,555 individuals with BD or schizophrenia and 54,065 controls.…”
Section: Polygenic Risk Score For Schizophrenia In Bdmentioning
confidence: 99%
“…Such a PRS might, in turn, be relevant to be studied in interaction with environmental risk factors that increase the susceptibility to the phenotype and/or the severity of the phenotype. Even though few studies have been published yet, it is suggested that a high PRS‐BD might be associated with some indicators of the severity of the clinical expression in BD, such as the presence of psychotic features during mood episodes, while PRS‐BD has been suggested not to be associated with an earlier age at onset, another indicator of clinical severity …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one could argue that the higher percentage of females diagnosed with BD-II could interfere with the gender distribution of the samples analysed, and therefore be the cause of our ndings. However, of note, Bobo et al, 32 Buoli et al, 33 Karanti et al, 27 and Vieta et al, 34 had a higher proportion of BDI patients in their samples, and Kalman et al 36 only had BDI patients in their sample. Findings of a higher prevalence of female patients in these four studies could further support our hypothesis, being BDI the type of BD traditionally more commonly associated with equal prevalence in the two genders.…”
Section: Discussionmentioning
confidence: 90%
“…34 Another study collected data from the ConLiGen database (n = 2,563), 35 while the last one included data collected from ConLiGen, Bonn-Mannheim and PsyCourse databases (n = 1,995, BDI patients only). 36 Nine out of ten studies analysed samples of both BDI and BDII patients, while one study only analysed a sample of BDI patients. All the evaluated studies described the general distribution of their samples in terms of gender, reporting a higher prevalence of female patients, with female patient proportions ranging from 57•4% (RENDiBi Study) to 65•0% (WAVE-BD) (Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%